Urgensi Penyelenggaraan Pilkada Pada Masa Pandemi Covid-19 Di Indonesia - David Greacy Geovanie; Ni Made Darmakanti (Universitas Pendidikan Ganesha, 2020)
The Covid-19 pandemic outbreak has threatened people's health and has an impact on the weakening of various sectors. With this condition, several administrative agendas have also been postponed, regional head elections have also not escaped attention. In an effort to break the chain of spreading Covid-19, the President called for maintaining distance and avoiding activities that involve large numbers of people. On the basis of these considerations and under urgent circumstances, through the power of the president a policy to postpone regional elections was also presented in the form of a Government Regulation in Lieu of a Law as a legacy effort.